The Key to Success in Scientific Research: Analysis of Software Tools for Planning and Execution of Research Grant Projects - Pagáčová, Katarína; Skraba, Andreas (Journal of Ecohumanism, 2025)
The planning and management of grant-funded scientific and research projects in academic settings pose significant challenges due to their complexity, financial transparency requirements, and the need for effective interdisciplinary collaboration. This research analyses and evaluates selected software tools tailored for project management, aiming to identify the most suitable solution for planning and implementing such projects. The research focused on widely-used tools within the Czech and Slovak markets. A multi-criteria evaluation methodology was employed, incorporating both weighted and unweighted scoring systems to assess seven identified criteria. Results indicate that Easy Project outperforms other tools due to its strong localisation, comprehensive resource management, and cost transparency, making it particularly suitable for grant-funded academic projects. The findings align with existing studies emphasising the importance of financial transparency, the role of communication tools, and the potential of technologies like digital twins and AI for project planning and optimisation. This research provides a foundation for improving project management practices and achieving greater success in scientific research initiatives.